2018
DOI: 10.1038/s41559-018-0680-6
|View full text |Cite
|
Sign up to set email alerts
|

China’s tuberculosis epidemic stems from historical expansion of four strains of Mycobacterium tuberculosis

Abstract: A small number of high-burden countries account for the majority of tuberculosis cases worldwide. Detailed data are lacking from these regions. To explore the evolutionary history of M. tuberculosis in China — the third highest TB burden country — we analyzed a countrywide collection of 4,578 isolates. Little genetic diversity was detected within the large M. tuberculosis population in China, with 99.4% of the bacterial population belonging to lineage 2 and three sublineages of lineage 4. The deeply rooted phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(173 citation statements)
references
References 74 publications
13
158
2
Order By: Relevance
“…Although L2 is dominant in Eastern Asia, interestingly the region did not appear to have played a prominent role in dispersal of this lineage, except in its exchanges with South Eastern Asia. A recently published study using a range of methods including Bayesian inference on a large regional sample found that the extant M.tb population in China traces to a limited number of introductions (Liu et al, ), which is consistent with our findings of relatively few exchanges of M. tb between Eastern Asia and other regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although L2 is dominant in Eastern Asia, interestingly the region did not appear to have played a prominent role in dispersal of this lineage, except in its exchanges with South Eastern Asia. A recently published study using a range of methods including Bayesian inference on a large regional sample found that the extant M.tb population in China traces to a limited number of introductions (Liu et al, ), which is consistent with our findings of relatively few exchanges of M. tb between Eastern Asia and other regions.…”
Section: Discussionsupporting
confidence: 91%
“…We estimate that L2 diversified in South Eastern Asia following migration from Eastern Africa at some point between 697 BCE and 20 BCE (Table 1, Figures 5 and S7). Previously published analyses of L2 phylogeography also inferred a Southeast Asian origin for the lineage (Liu et al, 2018;Luo et al, 2015).…”
Section: Major Events In Mtbs Migratory Historymentioning
confidence: 87%
“…The increase is more gradual in the L4 model, and declines to hovering just above R=1. This roughly coincides with a jump in effective population size estimated by Liu and colleagues for MTBC lineages indigenous to China (61). The decline of R for L4 beginning approximately 350 BP appears surprising, given the historically recorded rise of the White Plague in Europe from the 17 th -19 th century (62).…”
Section: Discussionsupporting
confidence: 86%
“…Kingman coalescent. These findings have deep implications for population genetic studies of MTB (also discussed in Morales-Arce et al 2019): 1) in the last five years, at least a dozen studies inferred the demographic history of different MTB populations(Pepperell et al 2013, Comas et al 2013, Bos et al 2014, Lee et al 2015Eldholm et al 2015, Kay et al 2015, Luo et al 2015, Merker et al 2015, Folkvardsen et al 2017, Merker et al 2018, Liu et al 2018, Bainomugisa et al 2018, O'Neill et al 2019.…”
mentioning
confidence: 94%
“…For example: 1) The Bayesian Skyline Plot (Drummond et al 2005) has been used to infer past population dynamics in tuberculosis outbreaks, finding evidence for constant population size (Bainomugisa et al 2018), rapid population growth (Eldholm et al 2015, Folkvardsen et al 2017 or slow population decline (Lee et al 2015). 2) Different methods have been used to infer the demographic history of the global MTB population (Pepperell et al 2013, Comas et al 2013, Bos et al 2014) and of single MTB lineages (Kay et al 2015, Luo et al 2015, Merker et al 2015, Merker et al 2018, Liu et al 2018, O'Neill et al 2019, finding evidence for population growth or for complex fluctuations that have been correlated with major events in human history such as the introduction of antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%